2013
DOI: 10.1177/155892501300800405
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of porous Carbon/Nickel Nanofibers for Supercapacitor

Abstract: Two polymer solutions of polyacrylonitrile, polyvinyl pyrrolidone, and Ni(CH 3 COOH) 2 in dimethylformamide were electrospun into ternary composite nanofibers, followed by stabilization and carbonization processes to obtain porous carbon/nickel composite nanofibers with diameters of 100-200 nm. The study revealed that carbon/nickel composite nanofibers were successfully prepared, which allowed nickel particles with diameters of 20-70 nm to be uniformly distributed in the carbon nanofibers. It was also observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Vanadium pentoxide (V 2 O 5 )/carbon nanofiber composites were prepared for supercapacitor applications [44]. It was observed that loadings of V [47]. They also observed a decrease in specific capacitance with increase in discharge current, e.g.…”
Section: Electrochemical Properties Of Comn 2 O 4 Nanofibers Based Elmentioning
confidence: 99%
“…Vanadium pentoxide (V 2 O 5 )/carbon nanofiber composites were prepared for supercapacitor applications [44]. It was observed that loadings of V [47]. They also observed a decrease in specific capacitance with increase in discharge current, e.g.…”
Section: Electrochemical Properties Of Comn 2 O 4 Nanofibers Based Elmentioning
confidence: 99%
“…The choice of nickel species as electrode materials is due to the cheapness, simplicity in production and low environmental impact. [27][28][29] In addition, it is well known that nickel species, directly grown and distributed along the CNF, improve the electrical conductivity of the carbon nanofibers and provide an appropriate surface polarity with an increase of carbon surface wettability. 30,31 Therefore, this means a better electrolyte accessibility at the electrode surface for improving the kinetic reaction at the electrode-electrolyte interface.…”
mentioning
confidence: 99%
“…By adding a gold salt into the precursor solution, our objective is to obtain polymeric fibers that contain AuNPs after the reduction of the gold salt and particle growth. Some examples of Pd‐ and Ni‐modified carbon fibers prepared by a procedure similar to that employed in this work can be found in the literature . A similar approach was employed for the synthesis of polyethylene oxide (PEO) fibers containing AgNPs, for which PEO itself played the role of the reducing agent.…”
Section: Introductionmentioning
confidence: 99%